2018
DOI: 10.1097/md.0000000000013535
|View full text |Cite
|
Sign up to set email alerts
|

A case report of endoscopic therapy for radiation-induced hemorrhagic gastritis in patient with recurrent hepatocellular carcinoma

Abstract: Rationale:Radiation-induced hemorrhagic gastritis is an infrequent cause of upper gastrointestinal bleeding and difficult to manage. The current standard treatment has not been well established.Patient concerns:We described a 32-year-old male patient with hemorrhagic gastritis induced by external radiotherapy for hepatocellular carcinoma recurrence.Diagnoses:The endoscopic examination showed a diffuse area of bleeding in the gastric antrum.Interventions:After failure of conventional hemostasis treatment, we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Shukuwa et al [ 18 ] described a case of RIHG successfully treated with APC. Liang et al also demonstrated successfully stopping hemorrhage with repeated endoscopic APC combined with low-dose polyglycerol sclerotherapy for a patient with RIHG secondary to treatment for recurrent hepatocellular carcinoma [ 19 ]. Ross et al [ 20 ] described combined therapy with APC and radiofrequency ablation for diffuse RIHG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Shukuwa et al [ 18 ] described a case of RIHG successfully treated with APC. Liang et al also demonstrated successfully stopping hemorrhage with repeated endoscopic APC combined with low-dose polyglycerol sclerotherapy for a patient with RIHG secondary to treatment for recurrent hepatocellular carcinoma [ 19 ]. Ross et al [ 20 ] described combined therapy with APC and radiofrequency ablation for diffuse RIHG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…RT for gastric cancer has several side effects, such as leukopenia, nausea, vomiting and diarrhea [ 12 ]. In addition, a serious complication is radiation-induced gastritis [ 13 ]. Radiation-induced gastritis usually occurs two to three months after initial radiation and can cause gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-induced gastritis usually occurs two to three months after initial radiation and can cause gastrointestinal bleeding. Its endoscopic findings are telangiectasia, mucosal edema and diffuse erythema of the mucosa [ 13 ]. In our case, diffuse erythema of the mucosa and telangiectasia were confirmed two months after the end of IMRT (Figures 4B , 4C ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APC is able to discharge energy by dispersing current without contact, which makes it well-suited for operating near fragile mucous membranes. Liang et al reported a case of hemorrhagic radiation-induced gastritis for which hemostasis was achieved by adding low-dose polidocanol sclerotherapy to APC (13). If a case is resistant to conservative treatment, surgical gastrectomy is effective.…”
Section: Discussionmentioning
confidence: 99%